State of the art and perspectives on traditional and emerging biometrics: A survey. Issue 6 (16th October 2018) - Traore, Issa; Alshahrani, Mohammed; Obaidat, Mohammad S.
Abstract : The last three decades have seen a shift and impressive progress in the biometric technologies landscape. Several major real‐world applications of biometrics have been released and are currently being used around the world. At the same time, several new biometrics modalities have emerged and have started making an impact in securing sensitive data, information, and systems. We present in this paper a survey of traditional and emerging biometrics by emphasizing their connection to human body parts, behavior, and cognition. A review of the state of the art in the key technologies is carried out along with a discussion of major applications currently available in the real world.